How to get Innovation System Work? Reflections on methodological issues - (:unkn) unknown (My University, 2008)
The main objective of APPRI Workshop was to analyse conditions for implementing alternative action-research practices in partnership for development, taking into account the difficulties of "official" research and of the rural world, faced with the major challenges of sustainable development in the South. One originality of APPRI was to compare experiences from rural zones of Africa, with those of the UNICAMPO Peasants' University set up 10 years ago in the Brazilian Nordeste, a semi-arid region where small holders' farms exhibit some major similarities with those in Drylands Africa. The "Peasants' University" concept was unanimously chosen as a place to unify partnership initiatives bringing together research, rural development officers, farmer's organizations and rural communities. These Peasants' Universities will be places of learning where a common vision is shared for implementing development and environmental improvement activities. The APPRI group unanimously accepted that technical and institutional innovation in partnership is paramount. It needs to be co-constructed from local know-how and scientific and technical knowledge. Information and communication between all those involved in development needs to be revised and strengthened for ore interactivity and efficiency in order to contribute to cultural recognition and social economic transformation of rural communities. L'objectif de l'atelier APPRI était principalement d'analyser les conditions de mise en œuvre de pratiques alternatives de recherche-action en partenariat pour le développement, prenant en compte les difficultés de la recherche «officielle» et du monde rural face aux grands enjeux du développement durable au Sud. Une originalité d'APPRI était de confronter les expériences des zones rurales africaines à celles de l'Université Paysanne UNICAMPO mise en place depuis 10 ans dans le Nordeste brésilien, région semi-aride où les petites exploitations familiales prése
Keywords: African Research